Occupational risk in knee osteoarthritis: a systematic review and meta‐analysis of observational studies - Wang, X; Perry, TA; Arden, N; Chen, L; Parsons, CM; Cooper, C; Gates, L; Hunter, DJ (Wiley, 2020)
Objective To assess the association between occupational exposures and knee osteoarthritis (OA).